1999
DOI: 10.1007/s005860050206
|View full text |Cite
|
Sign up to set email alerts
|

The active straight leg raising test and mobility of the pelvic joints

Abstract: Objective signs to assess impairment in patients who are disabled by peripartum pelvic girdle pain hardly exist. The purpose of this study was to develop a clinical test to quantify and qualify disability in these patients. The study examined the relationship between impaired active straight leg raising (ASLR) and mobility of pelvic joints in patients with peripartum pelvic girdle pain, focusing on (1) the reduction of impairment of ASLR when the patient was wearing a pelvic belt, and (2) motions between the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
210
1
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(225 citation statements)
references
References 19 publications
3
210
1
11
Order By: Relevance
“…Using the scoring system for the ASLR test as in the present study, it is previously shown that ASLR score can assess disease severity for patients with PGP [18]. Moreover, Mens and co-workers [19] demonstrated a relation between the ASLR test and mobility of the pelvic joints. Yet, none of these studies explains the mechanisms for how ASLR is associated to functioning or improvement.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Using the scoring system for the ASLR test as in the present study, it is previously shown that ASLR score can assess disease severity for patients with PGP [18]. Moreover, Mens and co-workers [19] demonstrated a relation between the ASLR test and mobility of the pelvic joints. Yet, none of these studies explains the mechanisms for how ASLR is associated to functioning or improvement.…”
Section: Discussionmentioning
confidence: 65%
“…Less than 5% of healthy subjects scores one or more on the test [17], and hence our cut-off of 4 or above must reflect a marked dysfunction. ASLR is stated to reflect functioning as for instance in transfer of load from the legs to the trunk [19], indicating that the test results are related to the neuromuscular activation patterns. On the other hand, to what extent the effect is limited to the specific task and muscles involved or a more general effect is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASLR is known to be primarily achieved by the rectus femoris (RF) 23) which originates in the anteroinferior iliac spine. Mens et al 24) conducted a dynamic analysis of pelvic motion during ASLR by X-ray examination. According to their results, the iliac in the elevated leg side rotated forward (pelvic nutation) at the center near the sacroiliac joint, and the iliolumbar ligament on the same side pulled the transverse processes of L4 and L5.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic instability, in this context, refers to a failure in the pelvic load transfer mechanism causing excessive pelvic joint movement, which has been verified by observing the displacement between the pubic bones on two-dimensional radiographs [21]. Ideally, the load transfer is supported by well coordinated neuromuscular and articular systems [22].…”
Section: Introductionmentioning
confidence: 99%